Presidential Threshold and Parliamentary Threshold Setting in Elections - Monteiro, Josef Mario (PT. Riset Press International, 2023)
This conceptual study aims to analyze Presidential Threshold and Parliamentary Threshold arrangements in elections from the regulatory aspect, the implications for the political rights of citizens and political parties and their comparison with other countries. The method used is normative juridical with a conceptual approach, statutory regulations, and comparative law. The legal materials are primary, secondary, and tertiary, then analyzed descriptively qualitatively. Based on the results of the research, it can be stated that by setting the Presidential Threshold and Parliamentary Threshold percentages, the right of citizens to participate in government, both to vote and to be elected in elections, has been limited so that from the perspective of people's sovereignty, it has created inequality or in other words, there is no equality, fair to citizens. Because presidential and vice-presidential elections and legislative elections are a consequence of the existence of a democratic system, it should be regulated by laws and regulations that are in favor of the interests of the people and not just camouflage for political elites who prioritize their groups only.